2014
DOI: 10.1016/j.tws.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Residual ultimate strength of cracked steel unstiffened and stiffened plates under longitudinal compression

Abstract: This paper numerically deals with the influence of cracks (in terms of length and location) on the ultimate compressive strength characteristics of unstiffened and stiffened plate elements used in thin-walled structures. The cracks were presumed to be through-thickness, having no contact between their faces and no propagation was allowed. A series of nonlinear finite element analyses was conducted using ANSYS commercial finite element code in which the Newton-Raphson method has been employed to solve the nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 20 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…(12)) is in the form of thermal bending and in-plane forces. This gives rise to three cases of interest for its solution.…”
Section: Solution Of Governing Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…(12)) is in the form of thermal bending and in-plane forces. This gives rise to three cases of interest for its solution.…”
Section: Solution Of Governing Equationmentioning
confidence: 99%
“…They considered compression for buckling, tension for fracture and concluded that the presence of crack affects the buckling load. The work of Rigo et al [12] shows the application of nonlinear finite element analysis to calculate the ultimate compressive strength of unstiffened and stiffened plates with through thickness cracks. They presented results for in-plane compressive strength as affected by the length and location of cracks.…”
Section: Introductionmentioning
confidence: 99%
“…First, appropriate mesh size of the models are selected. Second, study [4] indicates crack location can significantly affects the ultimate strength characteristics of unstiffened and stiffened plate elements subjected to axial compressive action. So, the reduction characteristics of ultimate strength of ship plates with cracks in different locations are compared.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Bayatfar et al (2014) numerically dealt with the influence of transverse cracks on the ultimate compressive strength characteristics of unstiffened and stiffened plate elements. (Ming Cai Xu et al 2014) presented residual ultimate strength assessment of stiffened panels with fixed cracks.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the projected length of the crack could be regarded as an important index for the influence of crack. (Rahbar-Ranji and Zarookian, 2014) From all the literatures mentioned above, it can be seen that most of studies (Paik et al, 2005;Paik, 2008Paik, , 2009Margaritis and Toulios, 2012;Bayatfar et al, 2014;Rahbar-Ranji and Zarookian, 2014;Wang, 2012a, 2012b) assume crack damage as transverse or longitudinal cracks, which are parallel to one edge of the relevant structures. However, there are few investigations conducted for inclined cracks that are more common in aging structures.…”
Section: Introductionmentioning
confidence: 99%